PERFORMANCE OF PRIVATE ISLAMIC ELEMENTARY SCHOOL TEACHERS IN DEPOK CITY IN TERMS OF REWARD, SELF-EFFICACY, AND ORGANIZATIONAL COMMITMENT - Lilis Badriah; Zaenul Muttaqin; Hendro Prasetyono; Syahfitri Purnama; Eigis Yani Pramularso; Rozita Che Rodi (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
Reward and self-efficacy are important factors in enhancing organizational commitment to optimize performance, including for private Islamic teachers who work to help shape a future generation of outstanding citizens. The purpose of this study is to examine how reward and self-efficacy influence teacher performance, mediated by organizational commitment, among teachers at private Islamic elementary schools in Depok. This quantitative study involved 105 teachers as respondents, utilizing a survey method for data collection. Data were collected via questionnaires and subsequently analyzed using the Partial Least Squares (PLS) method with the assistance of the SmartPLS 4.0 application. After data analysis, the results showed that teacher performance is partially and positively influenced by reward, although not significantly; self-efficacy has a partial, positive, and significant influence on teacher performance; and organizational commitment also has a partial, positive, and significant influence on teacher performance. Regarding the mediating relationship, it was demonstrated that organizational commitment partially mediates the effects of reward and self-efficacy on teacher performance. The theoretical implications of this study align with previous research, namely that if attention to reward and self-efficacy increases, organizational commitment will strengthen and teacher performance will improve. These findings highlight the importance of enhancing reward and self-efficacy to strengthen long-term commitment to the organization, thereby optimizing teacher performance. Keywords: organizational commitment, private Islamic elementary schools, reward, self-efficacy, teacher performance.   Abstrak Penghargaan dan efikasi diri merupakan faktor penting dalam meningkatkan komitmen organisasi agar kinerja menjadi lebih optimal, termasuk bagi guru swasta Islam yang bekerja untuk berkontribusi mencetak generasi penerus bangsa yang unggul. Tujuan penelitian ini adalah untuk mengkaji bagaimana reward dan efikasi diri memengaruhi kinerja guru yang dimediasi oleh komitmen organisasi para guru sekolah dasar Islam swasta di Depok. Penelitian kuantitatif ini melibatkan 105 guru sebagai responden dengan menggunakan metode survei dalam pengumpulan datanya. Data yang diperoleh dengan mengumpulkannya melalui kuesioner dan kemudian data dianalisis memakai metode Partial Least Squares (PLS) dengan bantuan aplikasi SmartPLS 4.0. Setelah dilakukan pengolahan data diketahui hasil bahwa kinerja guru dipengaruhi oleh penghargaan secara parsial secara positif meski tidak signifikan, efikasi diri secara parsial memiliki pengaruh positif dan signifikan terhadap kinerja guru, dan komitmen organisasi juga secara parsial memiliki pengaruh positif dan signifikan terhadap kinerja guru. Dalam hubungan mediasi, dapat dibuktikan bahwa komitmen organisasi secara parsial memediasi pengaruh penghargaan dan efikasi diri terhadap kinerja guru. Implikasi teoretis penelitian ini sejalan dengan penelitian sebelumnya, yaitu bahwa jika perhatian terhadap penghargaan dan efikasi diri meningkat, komitmen organisasi akan menguat dan kinerja guru akan meningkat. Temuan ini merekomendasikan pentingnya meningkatkan penghargaan dan efikasi diri guna memperkuat komitmen jangka panjang terhadap organisasi sehingga kinerja guru akan lebih optimal. Kata Kunci: efikasi diri, kinerja guru, komitmen organisasi, penghargaan, sekolah dasar Islam swasta.